2012
DOI: 10.12659/msm.882463
|View full text |Cite
|
Sign up to set email alerts
|

Thermal ablation of unresectable liver tumors: Factors associated with partial ablation and the impact on long-term survival

Abstract: SummaryBackgroundThermal ablation procedures, including radiofrequency ablation (RFA) or laser-induced interstitial thermotherapy (LITT), are now well established in the treatment of malignant unresectable hepatic tumors. But the impact of partial ablation (PA) on long-term survival following computed tomography (CT)-guided radiofrequency ablation and laser- induced interstitial thermotherapy of unresectable malignant liver lesions and the associated risk factors of PA remain partially unknown.Material/Methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…3 shows an example of an incomplete ablation in one of our patients, most likely due to the adjacency of the liver vein and thus the heat sink effekt. Several studies investigated risk factors associated with partial ablation and local recurrence [23][24][25][26]. To our knowledge, there is no previous study investigating the detectability of the target lesion as a potential risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…3 shows an example of an incomplete ablation in one of our patients, most likely due to the adjacency of the liver vein and thus the heat sink effekt. Several studies investigated risk factors associated with partial ablation and local recurrence [23][24][25][26]. To our knowledge, there is no previous study investigating the detectability of the target lesion as a potential risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival after thermal ablation is 44% if the ablation is complete and 20% if it is partial. The frequency of partial ablation ranges from 38% to 52% [114][115][116]. The size of neoplastic mass is the main predictive factor for the completeness of the ablation, with better results achieved in metastases smaller than 3 cm [116,117].…”
Section: Nonsurgical Treatment Of Liver Metastases Of Colorectal Cancermentioning
confidence: 99%
“…Studies have reported local tumor progression rates of up to 40% at 12 months follow-up [16]. This might be explained by persisting difficulties regarding the optimal timing and imaging method during the procedure and for follow-up [17,18].…”
Section: Introductionmentioning
confidence: 99%